Treatment with sumatriptan 50 mg in the mild phase of migraine attacks in patients with infrequent attacks: a randomised, double-blind, placebo-controlled study - Tfelt-Hansen, P. (Springer-Verlag, 2006)
Most migraine patients with infrequent attacks are currently not treated with migrainespecific medication such as triptans. The response of these patients to triptans is unknown. The objective of this study was to investigate the efficacy and tolerability of sumatriptan 50 mg vs. placebo in migraine patents with infrequent migraine attacks when medication is taken during the mild phase of an attack. The study design was double-blind, placebocontrolled, parallel-group and randomised. Migraine patients were recruited by general practitioners and referred to one of 4 study centres. Additional patients were recruited by advertising. The patients were eligible for the study if they had between 6 and 12 migraine attacks with or without aura per year. The patients were instructed to take the medication during the mild phase of a single attack. The primary efficacy measure was the percentage of patients pain-free after 2 h. Fortysix percent of treated attacks were moderate or severe. In the intention-to-treat analysis, sumatriptan was superior (20/51 patients were pain-free) to placebo (8/47 patients pain-free) (p=0.03). Adverse events (AEs) occurred more frequently after sumatriptan (40%) than after placebo (13%) (p=0.003) and most AEs were mild or moderate. In this migraine population with infrequent attacks, sumatriptan was superior to placebo and was generally well tolerated.